Does Emotional Labor Matter for University Teaching? Examining the Antecedents and Consequences of University Teachers' Emotional Labor Strategies - Han, Jiying; Yin, Hongbiao; Yang, Xin; Wang, Feifei (Frontiers in Psychology, 2021)
Following Grandey's integrative model of emotional labor and emotion regulation, this study examined the relationships between university teachers' reported use of various emotional labor strategies and some antecedents (i. e., perceived emotional job demands and teaching support) and teaching efficacy. A sample of 643 university teachers from 50 public higher education institutions in an East China province responded to a questionnaire survey. The data analysis based on descriptive statistics and structural equation modeling showed that surface acting impeded teaching efficacy in instructional strategy and learning assessment, while deep acting and expression of naturally felt emotions enhanced teaching efficacy in course design, instructional strategy, and learning assessment. For the antecedents of university teachers' emotional labor strategies, teachers perceived that the emotional job demands of teaching facilitated their use of surface and deep acting; in contrast, teachers' perceived teaching support decreased their use of surface acting and increased their use of expression of naturally felt emotions.